AN ANALYSIS OF COMPOUND WORDS USED IN INFORMATION TECHNOLOGY FACILITIES (SEMANTICS APPROACH) - KURNIAWAN, TONI (2007)
In modern life, people find many facilities of technology, such as: in home, office, school, etc. In order to understand how to use the technology facilities, such as the manual book of Hand phone and Microsoft XP. In particular, in this research paper the researcher is analyzing the used of language of manual book of Hand phone and Microsoft XP. However, the researcher focuses on the used of compound words. The theories used are the O'Grady and Dobrovolsky's and the palmer's theories. The type of this research is descriptive qualitative method. In collecting the data, the writer applied the reading and collecting. The several steps are done to analyze the data. In analyzing the forms of compound words, the steps are: analyzing with employing the tree diagram, analyzing the type, analyzing by paraphrasing. In analyzing the meaning, the steps are: using the features of meaning, determining the literal meaning, classifying the meaning into opaque and transparent meaning. The research paper result, there are 27 data from two manual books of Hand phone and Microsoft XP. The results are: 1) the most common compound forms are: noun compound (19 data), adjective compound (5 data), and verb compound (3 data). 2) the most compound meaning are: transparent meaning (20 data) and the rest is opaque meaning (7 data).